AUTO CRITIC WESTERN WORLDVIEW ABOUT ECONOMIC MAN CONCEPT IN THE NEOCLASSICAL ECONOMIC ERA - Khoirul Umam; Ahmad Havid Jakiyudin; Isma Aulia Roslan (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2024)
Western thought’s worldview of the concept of man has influenced much of the theoretical basis of science.  Without realizing it, the Western interpretation of the human concept still raises debates just like the concept of the economic man. The West’s failure to understand the concept of the economic man had an impact on economic problems in the neoclassical era. This study aims to analyze the worldview analogy of Western thinking about human nature from various figures and relate it to the context of economic problems in a neoclassical era. This study uses a conceptual approach. Western interpretations of human nature tend to be based on the nature of animals such as rational animals, zoon politicon, and homo sapiens. Meanwhile, in an economic aspect, humans are considered selfish, materialistic, self-interested, greedy, and always want to gain power. The worldview of various Western figures in interpreting human economics leads to the rationality of materialism. It can be said that the Western worldview fails in understanding the human concept. Failure to understand this concept raises complex economic problems in the neoclassical era such as scarcity, climate crisis, poverty, and welfare. Because human nature is uncontrollably exploiting nature through production activities to increase wealth is a main factor.